1993
DOI: 10.1128/aac.37.7.1432
|View full text |Cite
|
Sign up to set email alerts
|

Shedding of Clostridium difficile, fecal beta-lactamase activity, and gastrointestinal symptoms in 51 volunteers treated with oral cefixime

Abstract: Microbial changes including the shedding of Clostridium difficile, fecal 1-lactamase activity, and gastrointestinal symptoms were assessed in 51 healthy volunteers given 200 mg of cefixime twice daily for 8 days. The number of organisms of the family Enterobacteriaceae (means standard deviations) dropped from 6.9 1.1 to 3.9 1.8 log CFU/g of feces (P < 0.01), whereas counts of enterococci rose from 7.0 1.5 to 9.0 1.0 log CFU/g of feces (P < 0.01). Both counts returned to their initial levels 50 days after the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 13 publications
1
8
0
1
Order By: Relevance
“…Analysis of the toxin gene type showed that 8 (50%) of the 16 isolates were positive for tcdA and tcdB and that the other half lacked tcdA and tcdB (see Table S2 in the supplemental material ["First test" column]), although all the specimens were negative in the EIA (Table 2). Because the sensitivity of the EIA was not as high as 10 6 CFU/g of feces, the incidence of toxigenic strains might have been underestimated. The precise environmental signals modulating toxin expression remain unclear, but in vitro studies indicate that toxin expression may be enhanced by stressors, including antibiotics, catabolite repression, and sporulation (18,53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the toxin gene type showed that 8 (50%) of the 16 isolates were positive for tcdA and tcdB and that the other half lacked tcdA and tcdB (see Table S2 in the supplemental material ["First test" column]), although all the specimens were negative in the EIA (Table 2). Because the sensitivity of the EIA was not as high as 10 6 CFU/g of feces, the incidence of toxigenic strains might have been underestimated. The precise environmental signals modulating toxin expression remain unclear, but in vitro studies indicate that toxin expression may be enhanced by stressors, including antibiotics, catabolite repression, and sporulation (18,53).…”
Section: Discussionmentioning
confidence: 99%
“…This organism has been reported to be carried asymptomatically by 0% to 15% of healthy adults (10,11,20,36,37) and by 13% to 26% of hospitalized patients (30,31,42,52). C. difficile forms metabolically dormant spores to survive in unfavorable environments, such as conditions of aerobiosis, nutrient deficiency, dryness, or high temperature (16,22,54).…”
mentioning
confidence: 99%
“…Chachaty et al [43] konnte bei 51 gesunden Probanden, die über 8 Tage 2-mal täglich Cefixime erhielten, eine Zunahme von Clostridium-difficile-Nachweisen von 6 auf 57% und ein Rückgang auf 8% 50 Tage nach Absetzen der Antibiotikagabe zeigen.…”
Section: Patienten Und Methodenunclassified
“…According to the pharmacokinetic study of cefixime in rats, the bioavailability of cefixime was estimated at 30% (data not shown) and comparable to the rat and human data previously described (18,39), so the part excreted in the gastrointestinal tract may be considered approximately 70%. Based on these observations, we hypothesized that cefixime was hydrolyzed during transit by the ␤-lactamases-producing strains of anaerobic endogenous flora as previously described (11,26,42). We evaluated the impact of these ␤-lactamases by treating animals with cefixime together with clavulanic acid.…”
Section: Discussionmentioning
confidence: 99%